The Emergence of Artificial Intelligence in Indonesian Healthcare Services: Potential Uses and Possible Legal Risks - Falah Al Ghozali; Normalita Destyarini; Oktavia Eko Anggraini (Proceeding of International Conference on Science, Health, And Technology, 2022)
Artificial Intelligence (AI) is rapidly affecting the healthcare system that is more sophisticated. The emergence of AI in Indonesia still gives potential problem on legal risks. Indonesia with its Health Act has actually covered of the technology development, including AI. In fact, in practical aspect, the legal risks coming out from AI malpractice is unclear to tackle. In different circumstances, AI technology has some potential uses which is beneficial for health service development, for instance, data management, drug creation, treatment design, nursing, etc. In this paper, the authors would like to analyze the legal risk possibilities resulting from AI technology in the field of medicine, then it would be synthesized into legal aspects and its legal basis, whether or not the existing AI-related laws should be strengthened in order to tackle the problem occurring from AI malpractice.